Geronimo Stilton: The Kingdom of Fantasy #3: The Amazing Voyage (HC) - Stilton, Geronimo (Kingdom of fantasy, #3, 2011)
Geronimo joins the effort to rescue Blossom, Queen of the Fairies, who has been kidnapped by the Queen of the Witches and taken to the Kingdom of Nightmares